MPAS-Dev/MPAS-Analysis: v1.2.5 - Xylar Asay-Davis; Milena Veneziani; Phillip J. Wolfram; Luke Van Roekel; Darin Comeau; Riley Brady; Joseph H Kennedy; gstreletz; stephenprice; Adrian K. Turner; kevin; Mark Petersen; et al. (Zenodo, 2019)
This will be the last version of MPAS-Analysis to support python 2.7 Major Enhancements Add comparison maps with WOA18 climatology #622 Add task for plotting T-S diagrams in ocean regions #617 Minor Enhancements Add customDirectory for diagnostics #612 Add custom config file to webpage #614 Adds sample config and jobscript file for compy #618 Clean-up Isolate requests import #610 Round dlat/dlon in mesh names to 3 digits #611 Add 'antarctic' and 'arctic' tags to tasks #613 Bug fixes Add missing config.html template #615 Fix copying properties in mask creation #620 Handle case where git command is not available #623 Contributors @xylar @milenaveneziani @bradyrx @vanroekel